Long-term culture of human mesenchymal stem cell-seeded constructs under ultrasound stimulation: evaluation of chondrogenesis. (20th September 2016) - Thakurta, Sanjukta Guha; Sahu, Neety; Miller, April; Budhiraja, Gaurav; Akert, Leonard; Viljoen, Hendrik; Subramanian, Anuradha
Abstract: As cartilage does not have the innate potential to regenerate, translatable approaches based on mesenchymal stem cells (MSC) hold great promise for cartilage repair. In this study human MSC seeded in polyurethane scaffold were differentiated to chondrocytes in the presence or absence of dexamethasone (DEX), TGF β 3 and with or without exposure of ultrasound (US) at a resonant frequency of 5 MHz for the first two weeks according to the study groups: group 1 (DEX, No US), group 2 (DEX, US), group 3 (DEX, TGF β 3) and group 4 (DEX, TGF β 3, US). After two weeks, constructs were cultured in absence of any DEX and TG β 3 for another six weeks with or without US stimulation. At 8 weeks, group 2 constructs possessed dynamic stiffness ( E *), aggregate modulus ( H a ) and permeability ( k ) of 0.74 ± 0.072 MPa, 0.14 ± 0.003 MPa, 1.27 × 10 −10 ± 3.501 × 10 −11 m 4 N −1 s −1 respectively with total glycosaminoglycan and collagen of 6.52 ± 0.149 μ g GAG μ g −1 DNA and 17.14 ± 0.642 μ g COL μ g −1 DNA, respectively. Synergism of US with TGF β 3 in group 4 led to a significant improvement ( p < 0.05) in the properties over group 2. Regression analysis showed that the combined biochemical properties correlated with the E * ( R 2 ∼ 0.8–0.96). Ultrasound enhanced the protein expression of SOX9 and COL-II. Immunohistochemical and histological analyses revealed the presence of COL-II and GAG, while stained negative for von kossa and oil o red. In conclusion, this work has shown that: (a) MSC-seeding on polyurethane scaffolds, the subsequent lineage specific differentiation of MSC, and the further culture of MSC derived chondrocytes, were all performed in a seamless step in a 3D environment; notably under US stimulation in the absence of exogenous growth factors and (b) constructs under US had an aggregate modulus ranging from 0.14 to 0.17 MPa and approximating 1/10th the value of native cartilage.